A RARE CASE OF SPINDLE CELL LIPOMA OF THE RIGHT ADRENAL GLAND - WH, Wan Mohd Hafez; MA, Masliza Hanuni (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Spindle cell lipoma is a rare variant of lipoma that usually arises from subcutaneous tissue of the posterior neck and shoulder. Some cases of spindle cell lipoma may be found in the intraabdominal and retroperitoneal areas. CASE We report a 58-year-old female who presented with right abdominal pain and distension for one month. CT scan of the abdomen was done and revealed a large right adrenal mass (16.5 cm x 13.7 cm x 20.5 cm), with normal hormonal workup. Right adrenalectomy was performed and histopathological examination (HPE) confirmed Spindle Cell Lipoma. CONCLUSION This case represents a rare case of adrenal Spindle Cell Lipoma, which presented as a large adrenal mass with normal biochemical workup.